2015
DOI: 10.1007/s12594-015-0237-0
|View full text |Cite
|
Sign up to set email alerts
|

Megaloolithus Dinosaur Nest from the Lameta Formation of Salbardi Area, Districts Amravati, Maharashtra and Betul, Madhya Pradesh

Abstract: The present paper contributes the new locality of a nest of sauropod dinosaur from fluvial sediments of the Lameta Formation of Salbardi area. On the basis of shape, size and microstructures of the shell, it is identified as Megaloolithus. The new locality is away from the known nesting sites of dinosaurs already been reported i.e., Nagpur and Jabalpur, therefore bears significance in reconstruction of palaeogeographic boundary of dinosaurs-nesting sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Mankar and Srivastava (2015) proposed a new basin of deposition for the Lameta sediments in central India, viz., Salbardi-Belkhar inland basin and identified three different lithofacies reveling fluvial-lacustrine set-up for the same. Dinosaur remains and egg nests have been reported in recent studies (Srivastava and Mankar, 2015;Aglawe and Lakra, 2018;Fernández and Khosla, 2015;Khosla et al, 2015). Sonkusare et al (2016) reported plant remains and diverse spores and pollens within Lameta sediments.…”
Section: Marine and Continental Deposits In Bagh Group And Lameta Formentioning
confidence: 88%
“…Mankar and Srivastava (2015) proposed a new basin of deposition for the Lameta sediments in central India, viz., Salbardi-Belkhar inland basin and identified three different lithofacies reveling fluvial-lacustrine set-up for the same. Dinosaur remains and egg nests have been reported in recent studies (Srivastava and Mankar, 2015;Aglawe and Lakra, 2018;Fernández and Khosla, 2015;Khosla et al, 2015). Sonkusare et al (2016) reported plant remains and diverse spores and pollens within Lameta sediments.…”
Section: Marine and Continental Deposits In Bagh Group And Lameta Formentioning
confidence: 88%
“…Brookfield & Sahni (1987) later discarded this view and concluded that the Lameta sediments were deposited in an alluvial plain environment under semi-arid conditions, which has since been corroborated by Tandon et al (1990), Mohabey, Udhoji & Verma (1993), Mohabey & Udhoji (2000), and Mohabey & Samant (2003), among others. The rich terrestrial flora and fauna recovered from the Lameta Formation, including rich skeletal remains of sauropod and theropod dinosaurs as well as their eggs, nests, and coprolites, similarly indicate a semi-arid climate and fluvial-lacustrine environments (Mohabey, 1987;Mohabey, 1996;Srivastava & Mankar, 2015;Tandon et al, 1995). A Maastrichtian age has been suggested for the Lameta Formation of Pisdura and Dongargaon on the basis of dinosaur skeletal remains, nests, eggs, coprolites, ostracods, charophytes, diatoms, and plants (Mohabey, Udhoji & Verma, 1993;Ambwani et al, 2003;.…”
Section: Geological Settingsmentioning
confidence: 99%
“…These authors suggested that as India, Madagascar and South America were well separated from each other by 100-90 Ma, the wide distribution of similar taxa in these landmasses indicates their origin and dispersal prior to the separation of these landmasses or that there were some yet to be identified land connections between these southern terranes. Srivastava and Mankar (2015) documented the presence of a single nest of Megaloolithus (sauropod dinosaur) in the Lameta Formation from a geographic site located at the boundary of Amaravati District in Maharashtra and Betul District in Madhya Pradesh, quite far away from the traditionally known nesting sites of Jabalpur, Bagh, Balasinor, and Dongargaon. In a major taxonomic reassessment of the purported large lizard nest found in association with sauropod nests in the Lameta Ghat section of the Lameta Formation at Jabalpur, reassigned it to crocodiles.…”
Section: Late Drift Phasementioning
confidence: 99%